Melatonin functions as a broad‐spectrum antifungal by targeting a conserved pathogen protein kinase. Issue 1 (9th November 2022) - Li, Renjian; Bi, Ruiqing; Cai, Huanyu; Zhao, Juan; Sun, Peng; Xu, Weilong; Zhou, Yaru; Yang, Wei; Zheng, Lu; Chen, Xiao‐Lin; Wang, Guanghui; Wang, Dongli; et al.
Abstract: Melatonin is a low‐cost natural small indole molecule with versatile biological functions. However, melatonin's fungicidal potential has not been fully exploited, and the mechanism remains elusive. Here, we report that melatonin broadly inhibited 13 plant pathogens. In the rice blast fungal pathogen Magnaporthe oryzae, melatonin inhibited fungal growth, formation of infection‐specific structures named appressoria, and plant infection, reducing disease severity. Melatonin entered fungal cells efficiently and colocalized with the critical mitogen‐activated protein kinase named Mps1, suppressing phosphorylation of Mps1. Melatonin's affinity for Mps1 via two hydrogen bonds was demonstrated using surface plasmon resonance and chemical modifications. To improve melatonin's efficiency, we obtained 20 melatonin derivatives. Tert‐butyloxycarbonyl melatonin showed a 25‐fold increase in fungicidal activities, demonstrating the feasibility of chemical modifications in melatonin modification. Our study demonstrated the broad‐spectrum fungicidal effect of melatonin by suppressing Mps1 as one of the targets. Through further systematic modifications, developing an eco‐friendly melatonin derivative of commercial values for agricultural applications appears promising.